Meningkatkan Minat Belajar Anak Melalui Metode Belajar MEDIDOOR - Berlianti; Hura, Tabita Loreansa (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Learning is an important aspect for every individual to be able to achieve hopes, ideals, and a good future. However, not all individuals want to study seriously, one of which is caused by the situation of boring learning activities. Not to mention that since the pandemic period, the process of teaching and learning activities in schools is very limited, namely only through zoom meetings so that students often find it difficult to understand the material. If this happens continuously, it will cause boredom in students and of course become a serious problem. The same thing happened to one of the children at the Ora Et Labora Nusantara Orphanage who needed help to increase his interest in learning. The process of providing assistance was also carried out in the PKL I mini project activities, using the casework method through the general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The focus of the client's problem solving process is the use of the MEDIDOOR learning method (Watching, Discussion, and Outdoor Learning) as a jointly designed strategy to increase the client's interest in learning. The purpose of this program was stated to be achieved, as evidenced by the increased enthusiasm for learning and the client's high curiosity about all kinds of knowledge.